Growth of Banana cv. Kayu (Musa paradisiaca cv. Kayu) Meristemoids on Various Type of Media In Vitro (Agrotrop : Journal on Agriculture Science, 2026)
Banana is an important fruit commodity in Bali that has high demand from the tourism sector and religious ceremonies. However, its availability has not been fulfilled continuously because local production is limited and still relies on supplies from outside the region. One of the efforts to provide quality seedlings and preserve local banana genetic resources is through tissue culture techniques. This study aimed to obtain the best media composition for the growth of Timber banana meristemoids in vitro. The research was conducted at the Tissue Culture Laboratory of the Faculty of Agriculture, Udayana University from February to November 2023, using a two-factor factorial design with five replications. The first factor was media type (MS, BMM, and AGS), while the second factor was growth regulator (Z0 = no ZPT, Z1 = BAP 5 ppm, Z2 = TDZ 2 ppm, Z3 = BAP 5 ppm + TDZ 2 ppm). Variables observed included shoot emergence, number of shoots, number of leaves, number of roots, and root length. The results showed no interaction between treatments, but MS media gave the best results in almost all variables observed. ZPT treatment significantly affected the number of leaves, with 2 ppm TDZ producing the best growth in the number of leaves, number of roots, and root length. Thus, MS media is the optimal media for in vitro culture of Timber banana meristemoids, while the use of 2 ppm TDZ is effective in increasing the growth of vegetative organs.
Keywords: Wood banana; Meristemoid; Media Type